Analisis Reaksi Maillard pada Pengawet Alami Pangan Kitosan Kombinasi Asap Cair Sekam Padi dengan Konsentrasi yang Berbeda - Maya Resta Kanya; Selly Ratna Sari; Yunita Sari; Muhammad Rama Nopan Ariyadi (Universitas Sumatera Selatan, 2023)
Preservatives are becoming one of the more frequently used food additives. Natural preservatives are needed to replace the use of formalin, which is hazardous to human health. One of the natural preservatives that can be utilized is chitosan solution combined with rice husk liquid smoke. The chitosan solution combined with rice husk liquid smoke with the addition of glucose and the sterilization process will produce a Maillard reaction that functions to increase the effectiveness of antibacterial properties. The research objective was to determine the level of browning of chitosan solution combined with rice husk liquid smoke as a natural food preservative. The research method used a completely randomized design (CRD) with 5 treatments repeated three times. The treatments used were: A0 (1% Chitosan + 1% Acetic Acid + 1% Glucose), A1 (1% Chitosan + 1% Acetic Acid + 1% Glucose + 1% Rice Husk Liquid Smoke), A2 (1% Chitosan + 1% Acetic Acid + 1% Glucose + 2% Rice Husk Liquid Smoke), A3 (1% Chitosan + 1%s Acetic Acid + 1% Glucose + 4% Rice Husk Liquid Smoke), A4 (1% Chitosan + 1% Acetic Acid + 1% Glucose + 6% Rice Husk Liquid Smoke). The results showed that chitosan combined with rice husk had a very significant effect on the browning index value. The higher the concentration of liquid smoke, the higher the result of the browning index produced. The Maillard reaction occurs due to the presence of aldehyde ketone compounds in the liquid smoke of rice husk meeting the free amino acid compounds of chitosan and glucose in the heating process so that the Maillard reaction can take place. The best concentration is treatment A4 which gets optimal results on the brownish index produced.